Profiling of phenolic compounds and antioxidant activities from Malaysian aromatic plants - Mat Jusoh, Hanapi; Haron, Normah (2018)
Phenolic compounds are plant-derived antioxidants that have the ability to reduce and prevent oxidative damage, owing to their free-radical scavenging properties. The present study aimed to determine total phenolic content (TPC), profile selected phenolic compounds and their antioxidant activities in five plants namely Citrus hystrix, Coriandrum sativum, Murraya koenigii, Polygonum minus and Ocimum basilicum in three different fractions - free, soluble bound and insoluble bound phenolic. The TPC was determined using Folin-Ciocalteu method and phenolic compounds were identified using high performance liquid chromatography (HPLC). The antioxidant activities were determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays. The result showed that the phenolic compounds such as gallic acid, ferulic acid, caffeic acid, sinapinic acid, p-coumaric acid and quercetin were detected in all fractions of the five plants at distinctive proportion. For majority of plants, phenolic acids extracted from soluble and insoluble bound phenolic fractions had higher concentrations compared to free phenolic fraction. P. minus showed the highest TPC in free (2.47 ± 0.57 mg GAE/g) and soluble bound (1.75 ± 0.57 mg GAE/g) phenolic fractions (p<0.05). Whilst, the highest TPC in insoluble bound phenolic fraction was shown by O. basilicum (1.99 ± 0.41 mg GAE/g) (p<0.05). In DPPH assay, P. minus had predominantly higher antioxidant activities in free (91.34 ± 0.94%) and soluble bound (90.31 ± 2.41%) phenolic fractions when compared to other plants (p<0.05). Whilst, O. basilicum was the excellent radical scavenger in insoluble bound (86.42 ± 2.90%) phenolic fraction (p<0.05). A similar trend was observed for ABTS antioxidant assay, where P. minus showed the maximum radical scavenging activities in free (85.87 ± 3.61%) and soluble bound (94.85 ± 4.13%) phenolic fractions. O. basilicum showed the highest radical scavenging activity in insoluble bound (77.36 ± 4.38%) phenolic fraction (p<0.05). These antioxidant capabilities can be correlated with the presence of phenolic acids. In fact, there were strong correlations between TPC and DPPH (r = 0.87) and TPC and ABTS (r = 0.86). In conclusion, all plants contained phenolic acids but only P. minus and O. basilicum had the highest phenolic contents with utmost antioxidant activities